Wastewater analysis for substance abuse monitoring and policy development - Prichard, Jeremy (CRC Press, 2021)
"This book will explain wastewater analysis (WWA) in the context of substance abuse; discuss the potential implications of WWA as a new method for understanding substance use in a variety of settings; and ignite a discourse with policy makers, criminologists, epidemiologists and other disciplines about the need for collaboration with WWA scientists"--